A Reinterpretation of the Crystal Structure Analysis of [K(crypt‐222)]+CF3−: No Proof for the Trifluoromethanide Ion. Issue 29 (26th April 2017) - Becker, Sabine; Müller, Peter
Abstract: Critically discussing and, if necessary, questioning results presented by other researchers has always been a vitally important process in science. Only through fruitful discourse does science arrive at broadly accepted hypotheses that finally become what we accept as scientific truth. In the spirit of this time‐honored tradition, we have examined the crystal structure as well as X‐ray diffraction data of the proposed compound [K(crypt‐222)] + CF3 −, which has recently been published. We arrived at the conclusion that the claim of the authors to have successfully and unambiguously characterized the ionic [K(crypt‐222)] + CF3 − through single‐crystal X‐ray diffraction is not sustainable. Even though it is possible that the original authors have indeed encountered the proposed species, the purpose of this report is to point out that the original authors cannot use the presented crystallographic data and model as proof for the existence of [K(crypt‐222)] + CF3 − . The reason for our conclusion is two‐fold: firstly, the crystal structure was not refined to established standards of good crystallographic practice and secondly, even if best practices of structure determination are employed, the submitted diffraction data do not allow establishing conclusively the true nature of the compound at hand. Recognizing that this gives charge unbalance we have not resolved, we nevertheless suggest an alternative molecular model, [K(crypt‐222)]⋅CHF3, to demonstrate the ambiguity of the diffraction data submitted by the original authors. However, because of this ambiguity, it is important to point out that the purpose of this report is not (and cannot be) the determination of the true nature of the compound at hand; we would merely like to demonstrate that an alternative interpretation of the original diffraction data is possible and, hence, that the conclusion drawn by the original authors is not unambiguously supported by their own data. Abstract : Playing devil's advocate : The recently published crystal structure of [K(crypt‐222)] + CF3 − is put to the test and its scientific impact is evaluated by a comparison with the alternative refinement model of [K(crypt‐222)]⋅CHF3 .